Exploring the Demographic and Professional Characteristics of Physicians and Nurse Practitioners Associated With Providing Medication-Assisted Treatment: A Retrospective Observational Study - Hannah L. Maxey PhD, MPH, RDH; Sierra X. Vaughn MPH; Analise Dickinson MPH; Robin Newhouse PhD, RN, NEA-BC, FAAN (SAGE Publishing, 2024)
Integration of medication-assisted treatment (MAT) for opioid use disorder in primary care settings is an emerging health care delivery model that supports increased access to specialized care but requires primary care provider engagement. Examining the characteristics of providers who provide this service is key to informing targeted recruitment. Using administrative and supplemental data collected during license renewal, this study aimed to identify the characteristics of primary care physicians and nurse practitioners (NPs) associated with greater odds of providing MAT in their practice. A retrospective observational study was conducted using a descriptive correlational design. The analysis included 5259 physicians and 3486 NPs who renewed their licenses electronically in 2021 and specialized in primary care or psychiatry. Chi-square and logistic regression analyses were conducted to identify the demographic and clinical characteristics of physicians and NPs associated with MAT participation in their practice. Physicians had a higher odds ratio (OR) of providing MAT if they were younger than 35 years (OR = 1.334; P  = .0443), practiced in a federally qualified health center (OR = 3.101, P  < .0001), and offered a sliding fee scale in their practice (OR = 2.046; P  < .0001). Likewise, NPs had higher odds of providing MAT if they practiced in a public or community health center (OR = 3.866; P  < .0001). The results of this study highlight the personal and professional characteristics of physicians and NPs associated with higher odds of providing MAT. These findings may have implications for the recruitment and sustainability of MAT integration in primary care.